Evaluation of LDH and Gamma Interferon as Biochemical Markers for Diagnosis of Pulmonary and Extra-Pulmonary Tuberculosis (Bangladesh Journal of Medical Biochemistry, 2018)
Tuberculosis is a common disease throughout the world, especially in developing countries. The most common form of the disease is pulmonary tuberculosis (PTB). Extra pulmonary tuberculosis (EPTB) is also a growing problem worldwide. The diagnosis of PTB and EPTB is even harder when smears and cultures are negative. Due to its nature, the diversity of clinical pictures, the diagnosis of EPTB is often difficult and late. Advances in rapid diagnostic techniques are urgently required both for the early management of the new cases of TB and for the individuals already infected with Mycobacterium tuberculosis and are at risk of developing disease. In addition to standard TB diagnostic techniques, use of new biochemical surrogate markers like LDH and gamma interferon are new suggested. This study was undertaken to evaluate the diagnostic value and accuracy of serum LDH and gamma interferon for the diagnosis of PTB and EPTB. This crosssectional study was carried out in the Department of Pathology and Microbiology, NIDCH, Dhaka and by convenient and purposive sampling, 131 patients (male 98, female 33) having age range of 20-90 years were enrolled for the study. Serum LDH and QuantiFERON-TB gold (QFT-G i.e. gamma interferon) were estimated and the result was compared with the culture and histopathology results. Performance tests were done. Prevalence was measured at 95% CI. Statistical significance was set at p